Detection of viral agents in cerebrospinal fluid in pediatrics: 7 years of experience (Actualizaciones en Sida e Infectología, 2025)
The diagnosis of viral meningoencephalitis and encephalitis is a frequent challenge in pediatrics and the establishment of viral etiology by polymerase chain reaction (PCR) is important because it allows guiding treatment and avoiding the unnecessary use of antibiotics. We designed a retrospective study with the aim of describing the frequency of distribution of viral agents detected in cerebrospinal fluid (CSF) of children with suspected meningoencephalitis/viral encephalitis, assessing the percentage of HSV1-2 detection in second lumbar puncture when the first result was negative and correlating with the cytophysicochemical study. CSF samples collected in the period April 2017 to February 2024 from 590 hospitalized patients were analyzed with mutiplex PCR Meningitis/Encephalitis Panel (FilmArray, Biofire Diagnostics) and commercial techniques for HSV1-2. At least one viral agent was detected in 17% of the samples, with the highest frequency of Enterovirus: 10.8%, Human Herpes-6: 3.9% and HSV1: 1.9%. Patients with detectable PCR presented meningoencephalitis: 53% and encephalitis 19%. In 22% of cases they were associated with other pathologies. All second samples (40/590) tested for HSV1-2 were negative. Cytophysicochemical tests showed no differences between cases of herpetic and non-herpetic encephalitis.
Keywords: Viral meningoencephalitis, Herpetic encephalitis, Cerebrospinal fluid, Herpes simplex virus, Viral diagnosis.